Testing, simulation and design of hot-rolled seamless austenitic stainless steel CHS columns. (June 2022) - Ning, Keyang; Yang, Lu; Sun, Yao; Sun, Yinan
Abstract: Stainless steel circular hollow section (CHS) members are favoured by architects and structural engineers because of their aesthetics, superior torsional resistance and corrosion resistance. Hot-rolling is one of the typical production processes for producing CHS members. Nevertheless, few research has been carried out concerning the hot-rolled stainless steel CHS members. This paper reports experimental and numerical investigations into hot-rolled seamless stainless steel CHS columns. Flexural buckling tests on eight columns were firstly carried out in the experimental investigation. This was followed by numerical modelling investigation, where the FE models were developed and validated against the test results. The validated FE models were then used to conduct a series of parametric studies to obtain more data covering a wide range of member slenderness and cross-section sizes. Based on test and FE results, three existing design approaches in the Eurocode, Chinese specification and American specification were assessed and discussed. The assessment results show that the three design approaches all provide relatively accurate strength prediction on the whole, but the design approaches in the 1993-1-4 + A2 and ANSI/AISC 370-21both give overestimated strength predictions while design approach in the CECS 410 gives a relatively conservative strength prediction when the column slenderness is small. In view of this, new column design curve has been proposed, with its advantage over the existing design approaches confirmed by quantitative and graphical comparisons.